Evaluating the Accuracy of Spatial Interpolation Methods in Creating Maps for the Distribution of Traffic Noise between Al-Thawra Street Tunnel and Al-Azhari Roundabout in Lattakia using GIS - عطَاف نورا; هيثم جناد; سامية شيبان (Latakia University Journal -Engineering Sciences Series, 2022)
Traffic noise is considered a harmful environmental pollution that has a serious impact on the quality of human life. The study aims to identify the parts most vulnerable to noise pollution and the quiet parts of the area between the Al-Thawra Street tunnel and Al-Azhari roundabout in Lattakia by creating noise maps. This is done by using some spatial interpolation methods (Natural Neighbor Interpolation (NNI), Inverse Distance Weighted (IDW) and Kriging) for the noise levels monitoring points in the study area. The data were collected in 223 sites by means of a noise measuring device (NTI-XL2) within the three time periods shown in the Syrian Standard Specification for noise 2016 (day, evening, night) all days of the week in the months (May - June - July - August (2020 and months). December - January - February - March) 2020-2021. The accuracy of the results of noise levels resulting from the interpolation methods was evaluated using a set of statistics: maximum, minimum, mean, standard deviation and Pearson coefficient, in addition to the mean ME, mean absolute error MAE and root mean square errors (RMSE), to arrive at the best way to represent noise levels. The result shows that the interpolation method (NNI) is the best in representing the noise levels in the study area.